Ethical Leadership in Managing AI-Integrated Library Environments - Sreeram, Anusha; Mehra, Ritika; Parashar, Komal; Rao, Bora Upendra; Mohapatra, Chinmaya Kumar; Jabbar, Meerja Akhil; Malagi, Veeresh (Indian Journal of Information Sources and Services, 2025)
The integration of Artificial Intelligence (AI) technology into library systems has transformed services such as intelligent cataloguing, user personalization, automated recommendations, and predictive analytics, all of which boost operational efficiency and user satisfaction. However, the application of AI technology raises serious concerns regarding ethics including but not limited to privacy, algorithmic discrimination, bias, and equitable accessibility. This paper aims to establish the importance of ethical leadership to actively govern AI-integrated library systems and other emerging technologies to enable responsible, inclusive, and sustainable AI innovation. We are proposing the EL-AIL Framework (Ethical Leadership for AI in Libraries) to enable this process which is built on four TIAS pillars (Transparency, Inclusivity, Accountability, and Sustainability). This framework offers actionable guidance for library leaders that wish to make ethically responsible decisions while grappling with AI governance complexities. It promotes ethical leadership, reinforces the management of participatory governance, safeguards user’s data rights, and aligns AI with fiduciary library principles of intellectual freedom, access equity, and community trust. The EL-AIL Framework is illustrated with applied case analysis of facial recognition as access control, automatic acquisition planning, and adaptive learning technologies in academic libraries. The model enables holistic innovative foresight in ethical leadership development within libraries by reinforcing professional obligations in the context of advancing technology.